Treatment of Kaposi Sarcoma-Associated Herpesvirus-Associated Cancers - Dittmer, Dirk P.; Richards, Kristy L.; Damania, Blossom (Frontiers in Microbiology, 2012)
Kaposi sarcoma (KS) is the most frequent AIDS-defining cancer worldwide. KS-associated herpesvirus (KSHV) is the etiological agent of KS, and the virus is also associated with two lymphoproliferative diseases. Both KS and KSHV-associated lymphomas, are cancers of unique molecular composition. They represent a challenge for cancer treatment and an opportunity to identify new mechanisms of transformation. Here, we review the current clinical insights into KSHV-associated cancers and discuss scientific insights into the pathobiology of KS, primary effusion lymphoma, and multicentric Castleman’s disease.